Pengaruh Pelatihan, Budaya Organisasi, dan Motivasi Intrinsik terhadap Prestasi Kerja Karyawan - Khoirul Arifin; Kusuma Chandra Kirana (Universitas Batanghari, 2022)
This research has a purpose to determine the extent of training, organizational culture, intrinsic motivation on the work performance of employees of PT. United Tractors Site Sungai Danau South Kalimantan. In this study using quantitative research methods. The data used in this study is a saturated sample which means that all employees are sampled with a total of 70 respondents, with the help of the SPSS 26 program. The tests used are validity and reliability tests to measure data quality, classical assumption test, multiple linear regression, hypothesis testing. The results of this study can be seen that training does not have a positive effect on employee performance, organizational culture does not have a positive effect on employee performance, intrinsic motivation has a positive effect on employee performance, and training, organizational culture, intrinsic motivation together have a significant positive effect on work performance. employees of PT. United Tractors Site Sungai Danau South Kalimantan. Conclusion From the t test shows that training does not have a positive effect on employee work performance, from the t test results organizational culture does not have a positive effect on employee performance, from the t test above, intrinsic motivation has a significant effect on employee performance, training, organizational culture, motivation Intrinsic to Employee Performance has a significant simultaneous effect on employee performance at PT. United Tractors Site Sungai Danau South Kalimantan